Group collaboration reduces delay discounting of intertemporal choices and its duration - Xiaowei Geng; Yating Zhao; Shiyuan Xu; Xinye Sun; Xiaolin Zhou (Judgment and Decision Making)
Many real-world intertemporal decisions involve a group of two or more individuals making consensual decisions through group collaboration. Here, we ask how group collaboration affects intertemporal choices. In two experiments, participants completed intertemporal choices individually first (the precollaboration phase). Then, participants were placed into groups of two or three and completed a similar intertemporal task, with the group arriving at a consensual decision on each trial (the group collaboration phase). Finally, participants once again completed the intertemporal choices individually (the postcollaboration phase). Results showed that after group collaboration, the delay discounting significantly decreased compared to before collaboration both at group level and at individual level. The effect of group collaboration on individual intertemporal choices was no longer discernible by 1 week later. Therefore, the current research demonstrates the effectiveness of group collaboration and provides a way to nudge both groups and individuals to make farsighted choices.